Molecular Determinants of Optical Modulation in ssDNA-Carbon Nanotube Biosensors - Krasley, Andrew T.; Chakraborty, Sayantani; Vukovic, Lela; Beyene, Abraham G. (Meeting abstracts (Electrochemical Society), 2025)
This study investigates analyte-mediated modulation of the fluorescence in single-stranded DNA (ssDNA) functionalized single-walled carbon nanotubes (SWCNT). SWCNT fluorescence can be selectively sensitized to the local chemical environment, which has served as a basis for the synthesis and application of SWCNT-based optical biosensors for a variety of biologically relevant compounds including dopamine, norepinephrine, serotonin, and oxytocin, among others. However, the mechanistic basis for fluorescence modulation of functionalized nanotubes by various classes of analytes remains incompletely understood. One class of optical biosensors that have been particularly successful in biological research includes (GT) N oligonucleotide functionalized SWCNTs that exhibit exquisite turn-on response to compounds that contain catechol-like motifs. In this study, we combine experimental and computational approaches to show that ligand binding alone is not sufficient for optical modulation in this class of synthetic biosensors. Instead, the optical response that occurs after ligand binding is highly dependent on the chemical properties of the ligands, resembling mechanisms seen in activity-based biosensors. Specifically, we show that in ssDNA-SWCNT catecholamine sensors, the optical response correlates positively with electron density on the aryl motif, even among ligands with similar ligand binding affinities. Importantly, despite the strong correlations with electrochemical properties, we find that catechol oxidation itself is not necessary to drive sensor optical response. We discuss how these findings could serve as a framework for tuning the performance of existing sensors and for guiding the development of new biosensors of this class. As a results of these explorations, we have been able to achieve an improved understanding of ligand-sensor binding dynamics and sensing mechanism. We expect that the insights gleaned from this work will contribute to the body of knowledge that underpins SWCNT-based optical sensors.